Five-year comparative study of thin-strut rapamycin-eluting bioabsorbable scaffold with metallic drug-eluting stent in porcine coronary artery - Liu, Yaokun; Zheng, Bo; Zhang, Bin; Ndondo-lay, Robert; Nie, Fangfang; Tang, Naijie; Miao, Yongsheng; Li, Jianping; Huo, Yong (Frontiers in Cardiovascular Medicine, 2022)
Objectives Using quantitative coronary angiography (QCA), optical coherence tomography (OCT), histomorphometry, and pharmacokinetics, this study tried to evaluate the safety and efficacy of Biomagic rapamycin-eluting bioabsorbable scaffold (BVS) in non-atherosclerotic porcine coronary arteries. Background Biomagic BVS is a new generation of thin-strut bioabsorbable scaffold. We conducted comparative study detailing pathological response, safety and efficacy of Biomagic BVS and the Firebird2 rapamycin-eluting cobalt-based alloy stent (DES) in a porcine coronary artery model. The animals were followed up at 14 days, 1, 3, 6, 12, 18, 24, 30, 36, 42, 48, 54 and 60 months after stent implantation. Methods A total of 143 devices (95 Biomagic and 48 Firebird2) were implanted in 2 or 3 main coronary arteries of 76 nonatherosclerotic swine and examined by QCA, OCT, light microscopy, and pharmacokinetics analyses at various time points. Results Vascular responses to Biomagic and Firebird2 were largely comparable at all time points, with struts being sequestered within the neointima. Inflammation was mild to moderate (with absence of inflammation at 1 month) for both devices, although the scores were greater in Biomagic at 6 to 36 months. Percent area stenosis was significantly greater in Biomagic than Firebird2 at all time points except at 3 months. The extent of fibrin deposition was similar between Biomagic and Firebird2, which peaked at 1 month and decreased rapidly thereafter. Pharmacokinetic study showed that coronary tissue sirolimus concentration remained above 2 ng/mg of tissue at 28 day. Histomorphometry showed expansile remodeling of Biomagic-implanted arteries starting after 12 months, and lumen area was significantly greater in Biomagic than Firebird2 at 36 and 42 months. These changes correlated with dismantling of Biomagic seen after 12 months. OCT images confirmed that degradation of Biomagic was complete by 36 months. Conclusions Biomagic demonstrates comparable long-term safety and efficacy to Firebird2 in porcine coronary arteries with mild to moderate inflammation. Although Biomagic was associated with greater percent stenosis relative to Firebird2 within 36 months, expansile remodeling was observed after 12 months in Biomagic with significantly greater lumen area at ≥36 months. Scaffold resorption is considered complete at 36 months.